2017
DOI: 10.1634/theoncologist.2017-0066
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blinded, Phase II Trial of Gemcitabine and Nab-Paclitaxel Plus Apatorsen or Placebo in Patients with Metastatic Pancreatic Cancer: The RAINIER Trial

Abstract: Lessons Learned. The addition of the heat shock protein 27 (Hsp27)‐targeting antisense oligonucleotide, apatorsen, to a standard first‐line chemotherapy regimen did not result in improved survival in unselected patients with metastatic pancreatic cancer.Findings from this trial hint at the possible prognostic and predictive value of serum Hsp27 that may warrant further investigation.Background.This randomized, double‐blinded, phase II trial evaluated the efficacy of gemcitabine/nab‐paclitaxel plus either apato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 13 publications
1
32
0
Order By: Relevance
“…Apatorsen, the Hsp27 inhibitor used in this study, has been added to several standard regimens and investigated in several cancer types. Randomized phase II studies in bladder and prostate cancer suggested a modest benefit , whereas no benefit was seen in combination with gemcitabine/nab‐paclitaxel in pancreatic cancer . Additional trials with several Hsp inhibitors are ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…Apatorsen, the Hsp27 inhibitor used in this study, has been added to several standard regimens and investigated in several cancer types. Randomized phase II studies in bladder and prostate cancer suggested a modest benefit , whereas no benefit was seen in combination with gemcitabine/nab‐paclitaxel in pancreatic cancer . Additional trials with several Hsp inhibitors are ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…toxicity [51]. However, clinical study reported that the treatment of OGX-427 to a standard chemotherapy regimen, did not result in increased survival in unselected patients with metastatic pancreatic cancer, but there was a trend toward prolonged progression-free survival and overall survival in patients with high baseline serum HSP27, suggesting that this therapy may warrant further evaluation in the subgroup [52].…”
Section: Antisense Drugmentioning
confidence: 99%
“…A modified ASO that is complementary to Hsp27 (OGX-427) has been developed, showing inhibition of tumor progression and enhancement of gemcitabine's efficacy in pancreatic cancer [36]. Thereafter, a phase II trial of OGX-427 plus gemcitabine and nab-paclitaxel in patients with metastatic pancreatic cancer was carried out and revealed that the addition of OGX-427 to chemotherapy had no improved effect in the first-line setting [37]. Thus, clinical trials of the ASO strategy, as a new therapy combined with conventional drugs for advanced states of pancreatic cancer, have not shown significant additional value for these patients, going against our expectations.…”
Section: Asomentioning
confidence: 99%